Adult Women’s Interest in Facial Skincare Using the Thread Lifting Method - Elvyra Yulia; Dwi Syifa Meilandari; Karen Anjasrian (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
This study aims to determine the factors that influence the interest of adult women in facial skincare using the thread lifting method. The population of this study was consumers who visited the clinic to do facial treatment thread lifting. The research sample was taken as many as 34 female consumers aged 30-60 years, who visited the clinic to do facial treatment thread lifting. The research method used was a descriptive quantitative method. Data were collected using a survey method. The survey in this study uses a closed questionnaire to get an overview of the aspects of wants, interests, needs, knowledge. The research instrument used a Likert scale with a range of 1-5 levels. The answers range from very positive (scale 5) to very negative (scale 1). Based on the results of the study showed that the interest of adult women in thread lifting large threads on indicators of need with a percentage of 78.7%. So, it can be concluded that the interest of adult women in thread lifting for facial skin care is in a good category.